Factors Determining the Strength of Organizational Culture from Togetherness, Intensity and Morale - Palovac, Vladisik (International Journal Papier Public Review, 2020)
This article discusses the factors that determine the strength of public organizational culture in terms of togetherness, intensity and morale. The method used is a mix of methods or a mixture of qualitative and quantitative. Togetherness increases if work is done together outside the room, but morale has the same inside and outside the room, but togetherness will be high if work activities are carried out outside. Organizational culture is a reflection of the formal and informal organizations formed within the organization concerned. Togetherness and group dynamics, namely encouraging their work not to be individualized and the center of power not in one hand. The main step that we really need to do is to select the best seeds or the best employees to be united into a team. However, keep in mind that good employees don't mean they don't have any shortcomings.